Check-list of Anteoninae R. Perkins, 1912 (Hymenoptera: Dryinidae) of South Korea, with description of a new species - Kim, Chang-Jun; Lee, Jong-Wook (Zootaxa, 2014)
The subfamily Anteoninae (Hymenoptera: Dryinidae) was represented in South Korea by fifteen species belonging to the genus Anteon Jurine, 1807. In this paper, further eighteen species belonging to two genera are recognized for the first time from South Korea: Anteon worakense Kim & Lee, sp. nov., A. albonigrum Olmi, 1995; A. autumnale Olmi, 1991; A. devriesi Olmi, 1998; A. exiguum (Haupt, 1941); A. gaullei Kieffer, 1905; A. hikense Olmi, 1995; A. ingenuum Olmi, 1984; A. japonicum Olmi, 1984; A. metuendum Olmi, 1987; A. nanlingense Xu, Olmi & He, 2011; A. peterseni Olmi, 1984; A. songyangense Xu, He & Olmi, 1998; A. sulawesianum Olmi, 1991; A. wushense Olmi, 1991; A. yuani Xu, He & Olmi, 1998; Lonchodryinus infuscatus Xu, Olmi & He, 2009; L. ruficornis (Dalman, 1818). A. exiguum (Haupt, 1941) is also recorded from Russian Far East (new record). A check-list and a key to South Korean species of Anteoninae are presented.